Systematic Literature Review: Pemanfaatan Virtual Reality (VR) Sebagai Alternatif Media Pembelajaran - Poltak Gultom; Agus Salim; Rusmin Nuryadin (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Virtual Reality (VR) is not new in today's digital era. This technology has developed very quickly and has penetrated into many aspects of life, such as education. In this article, researchers reviewed current and previous research, to understand the extent to which Virtual Reality (VR) technology is used as an alternative learning media in educational institutions using the Systematic Literature Review (SLR) method by defining research questions as the first step. The search process was carried out from Scopus database using Publish or Perish 8 tools, and the selection of articles was based on inclusion and exclusion criteria related to the research questions. There were 200 articles found in the early stages of the search with a total of 22 articles that met the inclusion and exclusion criteria. The results obtained are in the form of a discussion of several aspects related to the use of virtual reality as a learning medium, such as: the type of technology, the location of educational institutions that use VR, learning domains, educational levels, evaluation techniques for learning with VR, and the purpose/benefit of its use.